ABNORMAL RETURN TRADING VOLUME ACTIVITY PADA PERISTIWA AMBRUKNYA FANNIE MAE DAN FREDDIE MAC - Dyah Ani Pangastuti (Jurnal Keuangan dan Perbankan, 2010)
The global economic crisis was a disaster for all nations in the world due to itsimpact once seemed to hamper the economy of a nation. This research studied the eventsthat would see if there was an effect of global economic crisis preceded by the U.S. Financialcrisis was triggered by the collapse of Fannie Mae and Freddie Mac in the property business(subprime mortgages) on September 7th, 2008. This study used samples that had been pub-licly traded company listed on the Indonesia Stock Exchange and entered into the sequenceof LQ-45 in the year of 2008. Hypothesis testing used was t-test on the average abnormalreturn and average trading volume of activity. Test results for the average abnormal returnshowed there were no significant differences before and after the Subprime Mortgage. Thetest results for the average trading volume of activity indicated the presence of a significantdifference before and after the Subprime Mortgage.